2001
DOI: 10.2466/pr0.2001.89.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Animal Research among Psychology Students in Spain

Abstract: Animal research plays a central role in psychology, and its use, prevalence and quality depends on the attitudes of students who enter psychology in Spain. Attitudes among psychology students about the use of laboratory animals are not known, so the aim of this work was to analyze the attitudes of Spanish psychology students toward animal research. An attitude questionnaire of 15 items was given to 661 undergraduate students of the School of Psychology at the University of Málaga, Spain. Several results were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
5
14
1
Order By: Relevance
“…Evaluations of demographic features of the responses allow us to refine our understanding of both student and faculty attitudes and their confidence in knowledge, and compare our respondent populations with those surveyed for other publications. A uniform finding in all studies that have looked at gender, including ours, is a greater prevalence of support among men for animal research [1820,32,33,4247]. We also observed that, among students, men found the issue of animal research less important than women, but, interestingly, this was not observed among faculty.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Evaluations of demographic features of the responses allow us to refine our understanding of both student and faculty attitudes and their confidence in knowledge, and compare our respondent populations with those surveyed for other publications. A uniform finding in all studies that have looked at gender, including ours, is a greater prevalence of support among men for animal research [1820,32,33,4247]. We also observed that, among students, men found the issue of animal research less important than women, but, interestingly, this was not observed among faculty.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, compared to the general public, our respondents had a higher average level of education. Higher education has been associated with greater support for animal research [3234]. However, our university is comparable to many other doctoral universities at which a large fraction of all animal research is conducted, so our findings should be generalizable to other members of this group.…”
Section: Discussionmentioning
confidence: 80%
“…Sex identity has been consistently found to relate to attitudes toward the treatment of research animals (and animals in general), with virtually all studies reporting that women are more likely to object to animal use [ 12 , 25 , 26 , 31 , 32 ]. A lower proportion of women accept the use of animals in research compared to men [ 27 , 33 , 34 , 35 , 36 , 37 ] and most studies of the animal protection movement have found that women activists outnumber men by a ratio of two or three to one [ 38 , 39 , 40 ]. The effects of sex identity on attitudes toward the use of animals in research are consistent across many studies, with differences between males and females extending to at least 15 different countries [ 14 ].…”
Section: Personal and Cultural Characteristicsmentioning
confidence: 99%
“…Th e evidence has consistently indicated that women are less supportive of animal research than are men (see Broida, Tingley, Kimball, & Miele, 1993;Navarro, Maldonado, Pedraza, & Cavas, 2001;Swami, Furnham, & Christopher, 2008). For example, Furnham and Pinder (1990) found women to be less supportive of animal research than men, as did Wells and Hepper (1997).…”
mentioning
confidence: 99%